2011
DOI: 10.1090/s0002-9939-2011-11080-3
|View full text |Cite
|
Sign up to set email alerts
|

Flat pseudo-Riemannian homogeneous spaces with non-abelian holonomy group

Abstract: We construct homogeneous flat pseudo-Riemannian manifolds with non-abelian fundamental group. In the compact case, all homogeneous flat pseudo-Riemannian manifolds are complete and have abelian linear holonomy group. To the contrary, we show that there do exist non-compact and noncomplete examples, where the linear holonomy is non-abelian, starting in dimensions ≥ 8, which is the lowest possible dimension. We also construct a complete flat pseudo-Riemannian homogeneous manifold of dimension 14 with non-abelian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…
We show that a complete flat pseudo-Riemannian homogeneous manifold with non-abelian linear holonomy is of dimension ≥ 14. Due to an example constructed in a previous article [2], this is a sharp bound. Also, we give a structure theory for the fundamental groups of complete flat pseudo-Riemannian manifolds in dimensions ≤ 6.
…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…
We show that a complete flat pseudo-Riemannian homogeneous manifold with non-abelian linear holonomy is of dimension ≥ 14. Due to an example constructed in a previous article [2], this is a sharp bound. Also, we give a structure theory for the fundamental groups of complete flat pseudo-Riemannian manifolds in dimensions ≤ 6.
…”
mentioning
confidence: 90%
“…In an article [2] by Oliver Baues and the author, Wolf's unipotent representations for fundamental groups with abelian Hol(Γ) were generalized for groups with non-abelian linear holonomy. Also, it was shown that a (possibly incomplete) flat pseudo-Riemannian homogeneous manifold M with non-abelian linear holonomy group is of dimension dim M ≥ 8.…”
mentioning
confidence: 99%
“…Let B n,ω denote a simply connected Lie group with Lie algebra b n,ω . It is known that every compact flat pseudo-Riemannian homogeneous space M of split signature (k, k) can be realized as a quotient B a,ω /Γ, where a is an abelian Lie algebra (see Baues and Globke [2,Section 3]). An interesting open question along these lines is whether a compact flat pseudo-Riemannian homogeneous space M with split signature (k, k) and non-abelian fundamental group Γ can be realized as B n,ω /Γ, where n is some non-abelian 2-step nilpotent Lie algebra.…”
Section: Remark 58mentioning
confidence: 99%
“…More recent studies by Oliver Baues and the author [1,2,5,6] investigated among other things the holonomy groups of these spaces. For some time only M with abelian linear holonomy group (given by the linear parts of Γ) were known, and it was unknown whether M with non-abelian linear holonomy existed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation